IMPLIKASI KEWAJIBAN PELAKSANAAN PATEN TERHADAP PENYELENGGARAAN ALIH TEKNOLOGI - Radhyca Nanda Pratama; Dilla Nurfiana Astanti; Muh Ali Masnun (Keadilan : Jurnal Fakultas Hukum Universitas Tulang Bawang, 2019)
Technology has a central role in accelerating the development of a country. The need for technology is pursued through a technology transfer process. The purpose of this study was to analyze the implications of patent obligations on the implementation of technology transfer in relation to the principle of property law, namely the droit de suite. This research uses legal research methods using primary and secondary legal materials. The approach used is a statutory approach) and a conceptual approach to be analyzed in depth with a prescriptive method. The results of the research show that the provisions referred to in Article 20 of the Patent Law require special exemptions for patent holders in the form of Institute of Science and Technology in order to carry out obligations related to making products or using processes in Indonesia to support technology transfer. The recommendation from this research is that there is a need for an exception to Article 20 of the Patent Law, by providing room for foreign patent holders not to immediately fulfill the obligations in Article 20 of the Patent Law or to make amendments (amendments) to these provition. Keywords : Implications, Patents, Technology Transfer.